2021
DOI: 10.1200/jco.2021.39.15_suppl.10588
|View full text |Cite
|
Sign up to set email alerts
|

Testing for mutations in BRCA1 and BRCA2 among ovarian cancer patients at a diverse academic medical center.

Abstract: 10588 Background: Testing for mutations in BRCA1 and BRCA2 is recommended for all women with ovarian cancer (OC), given important implications for treatment and prognosis. Despite this recommendation, studies show that only a small percentage of OC patients (pts) undergo genetic testing (GT). In this study, we evaluated rates of genetics referral, counseling and testing among OC pts at an academic medical center. Our goal was to identify factors associated with lower rates of GT. Given the large Black populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated underutilization and sociodemographic disparities in GT, with rates ranging between 52% and 56% among eligible patients with breast cancer [3][4][5] and 30% and 40% among those with ovarian cancer. 9,[19][20][21] Increasing age, 3,4,19 Black or African American race, 5,9,10,19,21,22 and lack of commercial insurance coverage 9,10 also have been identified as negative determinants of GT for both tumor types. However, these studies have been limited to single-institution investigations, claims-based analyses among commercially insured individuals, and registry-based studies in select states.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated underutilization and sociodemographic disparities in GT, with rates ranging between 52% and 56% among eligible patients with breast cancer [3][4][5] and 30% and 40% among those with ovarian cancer. 9,[19][20][21] Increasing age, 3,4,19 Black or African American race, 5,9,10,19,21,22 and lack of commercial insurance coverage 9,10 also have been identified as negative determinants of GT for both tumor types. However, these studies have been limited to single-institution investigations, claims-based analyses among commercially insured individuals, and registry-based studies in select states.…”
Section: Discussionmentioning
confidence: 99%